Watermarking Techniques for Multimedia Authentication - Borges, Paulo Vinicius Koerich; Pizzio, Robinson; Mayer, Joceli (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg); 2005: Anais do V Simpósio Brasileiro de Segurança da Informação e de Sistemas ComputacionaisDO - 10.5753/sbseg.2005.21544, 2005)
Recently we have witnessed great interest in watermarking technologies. Watermarking can be seen as a solution to overcome many security and authentication problems. Several watermarking methods have been proposed in the literature. In this paper, we review some of these techniques and their applications, properties, advantages and shortcomings. Moreover, we indicate that watermarking technology needs to be joined to classical security methods in order to solve challenging problems in multimedia authentication and other applications.